Eksistensialisme di Era Digital: Filsafat Søren Kierkegaard dalam Gaya Hidup Kontemporer: Existentialism in the Digital Age: Søren Kierkegaard's Philosophy in Contemporary Lifestyle - Astageni, Empi Siloka; Wijanarko, Robertus (Undiksha, 2025)
The focus of this paper is to present the meaning of existentialism according to Søren Kierkegaard in relation to today's contemporary digital lifestyle. Kierkegaard emphasizes individual existence in personal choice and authentic life. This can provide a quality contribution for humans to examine the implications of the digital era on their human experience. The digital age sets aside the fact that humans are driven almost entirely by the virtual reality of social media and digital connectivity. Humans are faced with the challenge of how to protect their identity in an increasingly complex world. Digital platforms can both obscure and illuminate human existence anxiety. It can affect the human self-concept and the dimensions that exist within it. This paper aims to generate an understanding of how Kirkegaard's philosophy of existentialism can navigate the existential dilemma that the digital era brings to humans today. The method used in this paper is a qualitative approach through literature study. The author specifically explores writings about individuals in Kierkegaard's perspective and other supporting sources. The author finds that human efforts to interpret their existence determine the direction of human life. Connectivity in the digital era cannot completely thwart humans from giving meaning to their lives.